2023
DOI: 10.3390/pr11041091
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Emulsification Variables on Emulsion Characteristics Prepared through the Phase Inversion Temperature Method as Engine Fuel

Abstract: The effects of emulsification variables, such as surfactant type and heating/cooling emulsion processes, on the emulsification characteristics of silicone oil’s emulsions prepared by the phase inversion temperature method were investigated in this study. The water-in-oil (W/O) emulsions have been widely applied to enhance burning efficiency and reduce both pollutant emissions and fuel consumption. The silicone oil was emulsified with de-ionized water with the assistance of nonionic surfactants to form oil-in-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The mean droplet sizes were significantly reduced with the increased concentration of Tween 20 and Span 80, as shown in Figure 3. Lin et al [40] observed that the increase of the surfactant concentration resulted in the decrease of both the electrical conductance and PIT where an abrupt drop of electrical conductance occurred. The surfactant mixture of Tween 20 and Span 80 caused higher PIT values of the emulsions than that of Brij 30.…”
Section: Effects Of Surfactant Type On Mean Droplet Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The mean droplet sizes were significantly reduced with the increased concentration of Tween 20 and Span 80, as shown in Figure 3. Lin et al [40] observed that the increase of the surfactant concentration resulted in the decrease of both the electrical conductance and PIT where an abrupt drop of electrical conductance occurred. The surfactant mixture of Tween 20 and Span 80 caused higher PIT values of the emulsions than that of Brij 30.…”
Section: Effects Of Surfactant Type On Mean Droplet Sizementioning
confidence: 99%
“…However, the emulsion of silicone oil has previously only been used as heat transfer fluids or long-acting vitreous substitutes, etc. The fuel characteristics of the silicone oil emulsion prepared through the PIT method have never been found in the literature although Lin et al [40] investigated the effects of various emulsification variables on the emulsion characteristics of silicone oil emulsions. Moreover, the effects of surfactant characteristics and processes of heating/cooling emulsion during phase change on the fuel properties of silicone oil emulsion using the PIT methods [41,42] have not been studied before.…”
Section: Introductionmentioning
confidence: 99%